2004
DOI: 10.1210/en.2003-1441
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothalamic-Testicular Neural Pathway Is Influenced by Brain Catecholamines, But Not Testicular Blood Flow

Abstract: We previously reported the existence of a descending multisynaptic, pituitary-independent, neural pathway between the hypothalamus and the testes in the male rat. Stimulation of this pathway by the intracerebroventricular (icv) injection of IL-1beta or corticotropin-releasing factor blunts the testosterone (T) response to human chorionic gonadotropin (hCG). This response is mediated at least in part by catecholamine beta-adrenergic receptor activation. The present work was performed to further investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 52 publications
1
30
1
1
Order By: Relevance
“…Similarly, structures thought to control the production of gonadotropic hormones, including the periventricular preoptic and anteroventral periventricular nuclei (Wiegand and Terasawa, 1982) also showed significant complements of double-labeled cells. This distribution suggests that androgenic regulation of gonadotropinreleasing hormone release and reproductive behavior is not entirely restricted to components of the gonadal axis, but may also rely on concurrent regulation of both the neuroendocrine and autonomic-related branches of the PVN (Selvage and Rivier, 2003;Selvage et al, 2004, Ulrich-Lai et al, 2006. This is consistent with the disruptive effects of adrenalectomy and sympathetic blockade on testosterone secretion, androgenic regulation of gonadotropin-releasing hormone and luteinizing hormone release, and sexual behavior (reviewed in Kalra and Kalra, 1983;Levine et al, 1991;Herbison, 2006;and see Poggioli et al, 1984).…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, structures thought to control the production of gonadotropic hormones, including the periventricular preoptic and anteroventral periventricular nuclei (Wiegand and Terasawa, 1982) also showed significant complements of double-labeled cells. This distribution suggests that androgenic regulation of gonadotropinreleasing hormone release and reproductive behavior is not entirely restricted to components of the gonadal axis, but may also rely on concurrent regulation of both the neuroendocrine and autonomic-related branches of the PVN (Selvage and Rivier, 2003;Selvage et al, 2004, Ulrich-Lai et al, 2006. This is consistent with the disruptive effects of adrenalectomy and sympathetic blockade on testosterone secretion, androgenic regulation of gonadotropin-releasing hormone and luteinizing hormone release, and sexual behavior (reviewed in Kalra and Kalra, 1983;Levine et al, 1991;Herbison, 2006;and see Poggioli et al, 1984).…”
Section: Discussionmentioning
confidence: 72%
“…This result is of interest as this timing indicates that testosterone is being elevated by mechanisms other that the classical hypothalamus-pituitary-gonadal axis where the endocrine response has been reported to have lag phase of *40 min from stimulus to increased concentration of testosterone (Spratt et al 1988). Recent research in vivo (Selvage et al 2004) has identified direct neural links between the para-ventricular nucleus of the hypothalamus and the testes, and this adds further supports to the idea that the rapid increase in testosterone seen here could have been elicited via a direct neural pathway.…”
Section: Discussionmentioning
confidence: 89%
“…This influence is exerted via a neural brain-testicular pathway (Gerendai et al, 2000;Lee et al, 2002) whose activation by stress-like signals in the central nervous system (CNS) blunts Leydig cell responsiveness to LH-like agents such as human chorionic gonadotropin (hCG). While the mechanisms mediating the influence of this pathway on Leydig cell activity are not fully elucidated, we have shown that they involve CNS catecholamines and the paraventricular nucleus of the hypothalamus (Selvage et al, 2004b). Importantly, this pathway is completely independent of the pituitary (Ogilvie and Rivier, 1998;Rivier, 1999;Selvage and Rivier, 2003;Turnbull and Rivier, 1997).…”
mentioning
confidence: 84%
“…While the respective importance of these different mechanisms remains the object of intense research, the use of alcohol as a model of stress presents one distinct advantage: namely, that alcohol can inhibit Leydig cell function following its intracerebroventricular (i.c.v. ) injection at doses that do not reach the periphery and do not induce neuronal damage in the brain (Selvage et al, 2004a(Selvage et al, , 2004b. This influence is exerted via a neural brain-testicular pathway (Gerendai et al, 2000;Lee et al, 2002) whose activation by stress-like signals in the central nervous system (CNS) blunts Leydig cell responsiveness to LH-like agents such as human chorionic gonadotropin (hCG).…”
mentioning
confidence: 99%